“On-Time Autism Intervention”: A Diagnostic Practice Framework to Accelerate Access - Penney, Ashley M.; Greenson, Jessica; Schwartz, Ilene S.; Estes, Annette Mercer (Frontiers in Psychiatry, 2022)
It is well documented that autism can be reliably diagnosed by age 2 and that early signs emerge most often between 18 and 24 months. However, despite the increased awareness and focus on early diagnosis, the average age of diagnosis is over four years old, even later for Black children and those who are Medicaid-eligible. In this paper, we will propose a framework for accurate and accelerated autism diagnosis for children before age three. The proposed framework emphasizes a collaborative diagnostic process, which relies heavily on Birth to Three provider knowledge and expertise. Considerations for next steps are presented. This approach could increase access to diagnosis of young children soon after first signs of autism emerge.